Sustainable development in rural Poland from the perspective of environmental economics - Henryk Manteuffel (Economic and Environmental Studies (E&ES), 2013)
The author discusses issues of sustainable development in rural areas in Poland from the perspective of environmental economics. It is argued that the growths in the entropy of matter and energy which can be observed in urban areas is also increasing in rural areas. Expressions of this process are growing disorder in space management. Sustainable development indicators show development is rather unsustainable, while policy for sustainable development has not been very successful.
Keywords: 330; sustainable development; rural development; environmental economics